2005
DOI: 10.2486/indhealth.43.580
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship between Subjective Unpleasantness and Body Surface Vibrations Induced by High-level Low-frequency Pure Tones

Abstract: Human body surface vibrations induced by high-level low-frequency pure tones were measured at the chest and the abdomen. At the same time, the subject rated the unpleasantness that he had just perceived during the exposure to low-frequency noise stimulus. Examining the relationship between the measured vibration and the rating score of the unpleasantness revealed that the unpleasantness was in close correlation with the vibration acceleration level (VAL) of the vibration measured. Taking previous results into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
(37 reference statements)
0
13
0
5
Order By: Relevance
“…Although the levels of these vibrations ('noiseinduced vibrations') are not especially high, our previous study, in which lowfrequency pure tones were used as noise stimuli, suggested that noise-induced vibrations measured on the body surface at the chest or abdomen are closely related to the perception of vibration in the corresponding part of the body [19]. Taking the results by Inukai et al into account, it was deduced that the noise-induced vibrations primarily contribute to the vibratory sensation, and, through the vibratory sensation or together with other factors, secondarily contribute to inducing unpleasantness in persons exposed to high-level low-frequency noise [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the levels of these vibrations ('noiseinduced vibrations') are not especially high, our previous study, in which lowfrequency pure tones were used as noise stimuli, suggested that noise-induced vibrations measured on the body surface at the chest or abdomen are closely related to the perception of vibration in the corresponding part of the body [19]. Taking the results by Inukai et al into account, it was deduced that the noise-induced vibrations primarily contribute to the vibratory sensation, and, through the vibratory sensation or together with other factors, secondarily contribute to inducing unpleasantness in persons exposed to high-level low-frequency noise [20].…”
Section: Introductionmentioning
confidence: 99%
“…Energy propagating in the air takes the form of acoustic waves that are divided by frequency into ultrasound, audible sounds, and infrasound [2]. Noise is an undesirable, unpleasant, cumbersome, oppressive or harmful sound of excessive intensity affecting the organ of hearing, the other senses and other parts of the body or the whole body [3][4][5][6][7]. Proper development of the acoustic environment is based on the formation of acoustic conditions so that they are optimal from the point of view of health and human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, níveis elevados de pressão sonora causados por uma fonte geradora de ruído de baixa frequência afetam toda a superfície do corpo humano [4]. Os experimentos [4], [5] e [6] realizados por diversos pesquisadores permitem concluir que o corpo humano reage de forma mecanicamente linear a estímulos sonoros levados pelo ar [4].…”
Section: Introductionunclassified
“…A existência de uma relação subjetiva entre altos níveis de ruído de baixa frequência e sensibilidade ao ruído ainda motiva pesquisadores [5], [6] e [7]. Por se tratar de um efeito subjetivo, torna-se de difícil a sua mensuração.…”
Section: Introductionunclassified